Migrant Remittances and Household Wellbeing in Urban Zimbabwe - Bracking, Sarah; Sachikonye, Lloyd (International migration, 2010)
Evidence from household surveying in December 2005 in Harare and Bulawayo, Zimbabwe, indicates that a wide network of international migrant remitters are ameliorating the economic crisis in Zimbabwe by sending monetary and in‐kind transfers to over 50 per cent of urban households. The research combines quantitative measurement of scale and scope, with demographic and qualitative narrative to build a holistic picture of the typography of receiving and non‐receiving households. A complex set of interrelated variables helps to explain why some households do and others do not receive income and goods from people who are away, and the economic and social extent of their subsequent benefit from them. Moreover, the mixed methods approach is designed to capture inter‐household and likely macroeconomic effects of how households receive their goods and money; and of how they subsequently exchange (if applicable), store and spend it. Evidence emerges of a largely informal, international social welfare system, but one which is not without adverse inter‐household effects for some. These include suffering exclusion from markets suffering from inflationary pressures, not least as a result of other people’s remittances. This paper explores the role of remittances, within this internationalised informal welfare system which we can map from our household survey, in reframing vulnerability and marginalization differentially among and between our subject households.